Ricette e canoni di impaginazione del libro medievale. Nuove osservazioni e verifiche - Maniaci, Marilena (Scrineum, 2013)
In the specific field of book design, as well as for many other aspects of Medieval Greek and Latin book production, the lack of written sources and the various problems posed by their interpretation make it very difficult to define and understand the choices of book artisans and scribes. Our knowledge is based on a total of only five layout recipes – four Latin and a single Greek one – very far from each other in time and contents. They assess a few common rules and various key differences and lead to very different page presentations. The contribution aims to compare the standards prescribed by the surviving recipes and the way they are formulated and to test their application to Greek and Latin manuscript book production, commenting on the difficulties posed by their interpretation and proposing some solutions.